Estudo da Estrutura da Proteína SH do Vírus Sincicial Respiratório Humano: análise funcional da estrutura pentamérica por ferramentas de bioinformática - Araujo, Gabriela Campos de [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
The human Respiratory Syncytial Virus (hRSV) is the major cause of lower respiratory tract illnesses in children and elderly people worldwide. Its genome encodes 11 proteins including the surface protein F, G and SH which are responsible for entry and distribution of virus in the host cell. Among the protein surface, little is known about the function of protein SH. Knowing their structure and function is fundamental to a better understanding of its mechanism. The aim of this study was modeling and caracterization of the RSV SH protein and analysis of structural behavior in different environment : water and phopholipid bilayer for understanding and evaluating the formation of its pentameric structure. The SH protein model was generated by I-TASSER server, and its funcional and structural caracterisct was analyzed by PredictProtein and PsiPred. Molecular Dynimics Simulation were performed for analysis of hidrophobicit of protein central region, studies of the protein behavior on the membrane and pentamer formation. The SH protein model prediction resulted in a linear model with a helix-alpha between amino acid 20-42 and the anlysis performed by PsiPred indicated this region as transmembrane region. Molecular Dynamics Simulation showed that, when in solution,the proteína changes its linear conformations for globular conformation confirming the hydrophobicity of the central domain. The presence of the Sh protein itself or of the pentamer in bilayer resulted in a considerable decrease of the area per lipid, giving the chains less mobility and greater alignment. The pentamer simulation showed passage of water molecules through the pore in an environment where histidine residues H22 and H51 are protonated, indicating the dependence of this activity with the pH of the medium. Based on this analysis, it was proposed the structure tertiary and quaternary of the SH protein and, with the analysis of the ...

O Vírus Sincicial Respiratório Humano (hRSV) é o maior causador de infecções respiratórias agudas (IRAs) em recém-nascidos e crianças no mundo inteiro. Seu genoma codifica 11 proteínas entre as quais as proteínas de superfície F, G e SH que são responsáveis pela entrada e instalação do vírus na célula do hospedeiro. Entre as proteínas de superfície, pouco se sabe sobre a função da proteína SH. O objetivo do presente estudo foi realizar a modelagem e caracterização da proteína SH e análizar o seu comportamento estrutural em diferentes meios: água e bicamada fosfolipídica. O modelo da proteína SH foi gerado pelo servidor I-Tasser, e suas características funcionais e estruturais analisados pelo PredictProtein e PsiPred. Simulações de Dinâmica Molecular foram realizadas para análise da hidrofobicidade da região central da proteína, do seu comportamento em membrana lipídica e possível formação de oligômeros. Os resultados da predição do modelo da proteína SH resultou em uma estrutura linear com uma alfa-hélice compreendida entre os aminoácido 20-42 e as análises realizadas pelo PsiPred indicaram essa região como sendo uma região transmembrânica. As simulações de Dinâmica Molecular mostraram que, quando em solução, a proteína muda sua conformação linear para globular confirmando a hidrofobicidade do domínio central. A presença da proteína SH sozinha ou das cinco estruturas na bicamada resultou num decréscimo considerável da área por lipídeo, conferindo as cadeias menor mobilidade e um maior alinhamento. As simulações do pentâmero mostraram a passagem de moléculas de água pelo poro em ambiente onde os resíduos de histidinas H22 e H51 apresentaram-se na forma protonada, indicando a dependência desta atividade com o pH do meio. Com base nessas análises foi possível propor uma estrutura terciária e quaternária da proteína SH e, com as análises da formação pentamérica da...
Keywords: Proteína SH; RSV; Modelagem molecular; Dinamica molecular